Internet of Things Legal Perspectives - Weber, Rolf H.; Weber, Romana; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The Internet of Things as an emerging global Internet-based information architecture facilitating the exchange of goods and services is gradually developing. While the technology of the Internet of Things is still being dis-cussed and created, the legal framework should be established before the Internet of Things is fully operable, in order to allow for an effective introduction of the new information architecture. The regulatory framework must provide for provisions ensuring the security of the structure as well as the privacy of its users. Furthermore, legal barriers that may stand in the way of the coming into operation of the Internet of Things are to be considered. The Internet of Things has positive effects in different fields, such as the inclusion of developing countries in global trade and the use of search engines to the benefit of civil society.
Introduction: Internet of Things: Notion -- Technicity of the Internet of Things -- Economics Environment of the Internet of Things -- General Approaches for a Legal Framework: Introduction -- Self-Regulation -- International Legal Framework -- Security and Privacy: Definitions -- Security and Privacy Needs -- Privacy Enhancing Technologies (PET) -- Legal Challenges for a Privacy Framework -- Responsibility for Violations of Privacy -- Outlook -- Governance of the Internet of Things: Establishment of a Governing Structure -- Legitimacy and Inclusion of Stakeholders -- Accountability -- Allocation of Critical Resources -- Internet of Things as Tool of Global Welfare: Bridging the Digital Divide -- Implementing Search Engines -- Combating Product Counterfeiting -- Tackling Environmental Concerns -- Improving Health Conditions -- Securing Food Supply -- Monitoring Compliance with Labor Standards -- Concluding Observations.
Keywords: Law; Computers -- Law and legislation; Comparative law; Public law; Law; International & Foreign Law/Comparative Law; European Law/Public International Law; Legal Aspects of Computing